2012
DOI: 10.3402/fnr.v56i0.18891
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dietary habits after migration and consequences for health: a focus on South Asians in Europe

Abstract: BackgroundImmigrants from low-income countries comprise an increasing proportion of the population in Europe. Higher prevalence of obesity and nutrition related diseases, such as type 2 diabetes (T2D) and cardiovascular disease (CVD) is found in some immigrant groups, especially in South Asians.AimTo review dietary changes after migration and discuss the implication for health and prevention among immigrants from low-income countries to Europe, with a special focus on South Asians.MethodSystematic searches in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
138
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(160 citation statements)
references
References 82 publications
(150 reference statements)
13
138
2
7
Order By: Relevance
“…Almost all the (non-vegetarian) respondents agreed that they ate much more meat after arrival in Australia, confirming the common experience with many immigrants as described by research on migrant food habits (Holmboe-Ottesen & Wandel, 2012;Lesser et al, 2014;Wandel et al, 2008).…”
Section: What Has Changed Since Moving To Brisbane? Changes In Gustatsupporting
confidence: 53%
See 3 more Smart Citations
“…Almost all the (non-vegetarian) respondents agreed that they ate much more meat after arrival in Australia, confirming the common experience with many immigrants as described by research on migrant food habits (Holmboe-Ottesen & Wandel, 2012;Lesser et al, 2014;Wandel et al, 2008).…”
Section: What Has Changed Since Moving To Brisbane? Changes In Gustatsupporting
confidence: 53%
“…CALD communities have consistently been shown to have higher rates of dietrelated disease than majority populations in many industrialised countries (Anikeeva et al, 2010;Misra & Ganda, 2007;Misra & Khurana, 2011). Indian and other South Asian migrants in particular have been shown to be at a greater risk of overweight, central obesity and T2DM than host populations and other migrant communities in these countries (Holmboe-Ottesen & Wandel, 2012;Johansen et al, 2009;Kumar, Holmboe-Ottesen, Lien, & Wandel, 2004;Kumar, Meyer, Wandel, Dalen, & Holmboe-Ottesen, 2005; 3 See Appendix 2 4 Health screening is mainly for infectious diseases that are a threat to public health in Australia such as TB, HIV, hepatitis B, C and conditions requiring long-term health care (Joint Standing Committee on Migration, 2010) http://www.border.gov.au/Trav/Visa/Heal/meeting-the-health-requirement/healthexaminations; https://www.border.gov.au/about/corporate/information/fact-sheets/22health…”
Section: The Research Issuementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the missing ethnicity group data was explored and it revealed that 50,410 were free of CVD at baseline and 7,810 (15.5%) developed CVD in the followup period giving a rate similar to that in those with known ethnicity (13.4%). Another limitation was that we were unable to adjust our models for physical activity, diet, and family history of diabetes and CVD (which are known to vary by ethnicity) [6,32,43]. At the same time, the effects of many of these factors may act through BMI, BP, total cholesterol, HDL-c, hypertension and age of diabetes diagnosis, which we have adjusted for in the analysis.…”
Section: Discussionmentioning
confidence: 99%